Facts About Fluoride - Anne Kendall (EDIS)
Fluoride is important for healthy bones and teeth. It increases the density of bones and also can stimulate the growth of new bone. Fluoride increases the amount of minerals in our teeth and even can reverse the progression of dental cavities. People who don’t get enough fluoride have much greater rates of dental decay and cavities than those who get enough fluoride. Due to water fluoridation, almost one-half of American children have never had a cavity in their permanent teeth. This 2-page fact sheet was written by Anne Kendall [Casella], and published by the UF Department of Family Youth and Community Sciences, July 2013.